Cultured microalgae for the food industry : current and potential applications - Lafarga, Tomas; Acien, Gabriel (Academic Press, 2021)
Cultured Microalgae for the Food Industry: Current and Potential Applications is a comprehensive reference that addresses the current applications and potential uses of microalgae and microalgae-derived compounds in the food industry. The book explores the different steps of the subject, from strain selection and cultivation steps, to the assessment of the public perception of microalgae consumption and the gastronomical potential of this innovative resource. Readers will find coverage of microalgae biology, common and uncommon algae species, cultivation strategies for food applications, novel extraction techniques, safety issues, regulatory issues, and current market opportunities and challenges. This title also explores the gastronomic potential of microalgae and reviews current commercialized products along with consumer attitudes surrounding microalgae. Covering relevant, up-to-date research as assembled by a group of contributors who are experts in their respective fields, the book is an essential reading for advanced undergraduates, postgraduates, and researchers in the microbiology, biotechnology, food science and technology fields.